Emergency Portasystemic Shunting in Cirrhotics With Bleeding Varices — A Comparison of Portacaval and Mesocaval Shunts. Issue 2 (1989) - Soutter, D. I.; Langer, B.; Taylor, B. R.; Greig, P.
Abstract : Despite the best conservative measures available for the control of major variceal hemorrhage, some patients either continue to bleed, or rebleed early, and require emergency surgery. One hundred patients with cirrhosis and uncontrolled bleeding were treated with emergency portasystemic shunts between 1968 and 1983. Fifty eight patients had end-to-side portacaval shunts and 42 had Dacron interposition mesocaval shunts. Both groups were comparable with respect to age, sex and prevalence of alcoholism. There was an increased severity of liver disease as assessed by Child's class in the mesocaval group of patients. Overall in-hospital mortality was 31% with no significant difference demonstrated between the mesocaval group (28%) and the portacaval group (33%), nor between alcoholic cirrhotics (34%) and non-alcoholic cirrhotics (21%). Mortality rates based on severity of liver disease were: Child's A (1/6) 17%, Child's B (9/48) 19%, and Child's C (21/46) 46%. There was a statistically significant difference between Child's A & B and Child's C (p < 0.01). Four patients were lost to follow-up. No significant differences were found in 5 year survival by life table analysis comparing portacaval (39%) vs. mesocaval (28%) groups or alcoholic cirrhotics (36%) vs. non-alcoholic cirrhotics (29%). Encephalopathy in survivors was absent in 46%, mild in 28% and severe in 26% of patients. There was no significant difference in encephalopathy rates following portacaval or mesocaval shunting. Neither operation was clearly superior and choice of operation can be made on the basis of technical and anatomical factors and surgeon experience. Emergency shunting remains a useful option for patients with variceal bleeding refractory to other more conservative therapy, and is associated with acceptable early mortality and long term survival rates.